Society and University - Aranda Dioses, Edith (2014)
We analyzed the social representations constructed by the students of the School of Economic Engineering of the National University of Engineering about their university experience in the context of Peruvian society, we explored the ways of thinking, feeling and attitudes that these students assume about various aspects that involve the society/university relationship.